Ameliorating a Complex Urban Ecosystem Through Instrumental Use of Softscape Buffers: Proposal for a Green Infrastructure Network in the Metropolitan Area of Naples - Coppola, Emanuela; Rouphael, Youssef; De Pascale, Stefania; Moccia, Francesco Domenico; Cirillo, Chiara (Frontiers in Plant Science, 2019)
Green Infrastructure (GI) definition, deriving from the United States green infrastructure for hydro-geological rebalancing through imitating the nature stormwater management, was consolidated in Europe by GI Planning Guide. Nowadays GI can be considered a valid and meaningful approach for ameliorating urban complex ecosystems, and could also be considered as mitigation action of land consumption, according to the guidelines on the soil sealing of the European Commission (2012). The metropolitan area of Naples located in south Italy is characterized by an unauthorized and chaotic urban development. The land-use map reported an average of 30% of urbanization in the metropolitan area, rising up to 50–60% and as high as 98% in the north core area of the city. This high level of urbanization is directly related to the habitat fragmentation. The National Biodiversity Conservation Strategy defines several challenges and targets to counteract the biodiversity loss in Italy, identifying urban areas as places exposed to the greatest pressures on ecosystems. Therefore, the integration of different policies limiting habitat fragmentation, heat island effect and natural soil hydro-geological degradation into spatial planning, especially through green corridors and ecosystem enhancement in urban areas is an urgent need for the society. Spatial planning has to be renewed in metropolitan areas, where threats and weaknesses to biodiversity conservation are stronger than in any other place, according to the Law n. 56/2014, (Gazzetta Ufficiale della Repubblica Italiana, 2014) committing metropolitan cities to the enactment of General Territorial Plan. In the current paper, we aim at designing an ecological network for the metropolitan area of Naples one of the biggest city of southern Italy. The analyses include the adopted methodological procedure, i.e., ecological network analysis and design, and the introductory elements of a spatial analysis on a pilot ecological network of several patches. Finally, the paper illustrates the network analysis conceived as a monitoring system and also in future perspective, as a planning support system.